The Role of Notaries in Public Company Share Transactions In the Capital Market of the Indonesia Stock Exchange - Prasetyo, Seno; Hafidz, Jawade (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
This study aims to analyze: 1) The role of notaries in stock transactions of public companies in the Capital Market of the Indonesia Stock Exchange. 2) Obstacles faced by notaries in ensuring the validity and legal certainty of stock transactions in the capital market. This type of research is included in the scope of empirical legal research. The approach method in this study is a sociological legal approach. The types and sources of data in this study are primary and secondary data obtained through interviews and literature studies. The analysis in this study is prescriptive. The results of the study concluded: 1) The role of notaries in stock transactions of public companies in the Capital Market of the Indonesia Stock Exchange based on Article 15 paragraph (1) of Law Number 2 of 2014 concerning the Position of Notaries (UUJN), notaries are tasked with making authentic deeds required by laws and regulations, including in the Initial Public Offering (IPO) process and stock transactions. In addition, in accordance with Article 64 paragraph (1) of Law Number 8 of 1995 concerning Capital Markets, as amended by Law Number 4 of 2023 concerning Development and Strengthening of the Financial Sector (PPSK Law), notaries are recognized as a supporting profession for the capital market. In this capacity, notaries play a role in helping to prepare and ratify important legal documents, such as changes to the company's articles of association, minutes of the General Meeting of Shareholders (GMS), and share sale and purchase agreements, which are the legal basis for transactions on the IDX. 2) Obstacles faced by notaries in ensuring the validity and legal certainty of stock transactions in the capital market, such as inaccurate or incomplete data and documents, issuers' ignorance of regulations, rapid regulatory changes, the complexity of capital market transactions, limited access to digital information, and potential inconsistencies between national law and international practices. To overcome these challenges, solutions are needed such as better data validation, education for issuers, improving notary competency, collaboration with related parties, development of an integrated digital system, and alignment of national regulations with international standards. Thus, notaries can carry out their role optimally to create legality and legal certainty in capital market transactions.